Impact of Emotional Expression of Parents on their Children who have Specific Learning Disorders and the Role of Parental Educational Counseling Program - Al-Safory, Ola; Hussein, Hoda Abdo; Mowafy, Maha Abdul Rahman; Sarhan, Mai Diaa (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Children are the world’s real treasures; they should be cherished, well raised and given the chance to develop properly. Some of them in different countries all over the world are suffering from different forms of specific learning disorders, which can be extremely frustrating the school child especially if associated with parental high emotional expression. Objectives: The purpose of the study is to identify the relation between emotional expressions (EE) of parents and anxiety rate in their children with specific learning disorders (SLDs), and its correlation with serum cortisol level of the children. The effect of parental educational counseling program (PECP) on anxiety rate of children and parental emotional expression was studied. Methods: The study was carried out on 140 children with SLD to evaluate their anxiety rate by using Taylor anxiety scale of children, and measuring serum cortisol level. Data were collected from parents by emotional expression scale (EES). Taylor anxiety scale and EES were repeated for children and parents after conducting sessions of PECP. Results: Results of Taylor anxiety scale showed that 60% of studied children were suffering from morbid anxiety. Results of EES showed that 80% of parents were practicing high emotional expression. Scores of children on Taylor anxiety scale demonstrated significant drop from 33.06±10.4 to 25.85±10.4 after applying the intervention (P < 0.001). More than two thirds of parents became practicing low EE after receiving sessions of the interventional program PECP. Scores of parents on EES showed significant drop from 61.31±16.84 to 36.51±13.89 after PECP (P < 0.001). A statistically significant positive correlation between scores of Taylor anxiety scale and EES before PECP was found (R = 0.533), and also after PECP (R = 0.309). Average level of serum cortisol of children with SLD was 8.973+1.784 mcg/dl, and it was significantly higher in boys than girls (P < 0.05). Serum cortisol level of studied children was higher in children with morbid and severe anxiety (P < 0.001). Cortisol levels of children were significantly higher in those whose parents were practicing high EE. Serum cortisol level of children revealed positive correlation with each of their scores on Taylor anxiety scale (R = 0.771) and scores of parents on EES (R = 0.468). Conclusion: Results of this study proved presence of direct relation between anxiety in school children with specific learning disorders and high emotional expressions of their parents. Results concluded effectiveness of PECP in management of children’s anxiety and parental emotional expression. Key words: Specific learning disorders, Emotional expression, Anxiety disorder, Serum cortisol level.